Technopolitics of hatred: strategies used by conservative WhatsApp groups and scholarship holders in the 2018 and 2022 Brazilian elections: Technopolitics of hatred: strategies used by conservative WhatsApp groups and scholarship holders in the 2018 and 2022 Brazilian elections (Simbiótica. Revista Eletrônica, 2024)
The article results from a presentation given at the I Colloquium of Social Sciences and Psychoanalysis: Frontiers and Coasts in Contemporary Malaise, held at UFES in December 2022. On the occasion, we exposed our research agenda dedicated to the investigation of the use of digital platforms by conservative groups associated with the former president of the republic Jair Messias Bolsonaro and the writer Olavo de Carvalho. From an ethnographic investigation carried out since 2018 with Bolsonaro WhatsApp groups, we proposed a debate on platforming, data colonialism and life dating, related to surveillance capitalism and platform capitalism, resulting in the composition of a diagram of Brazilian technoconservatism. Following, we present some of the strategies that were used in WhatsApp groups that recognize themselves as conservatives and bolsonaristas during the Brazilian elections (2018 and 2022).
Keywords: technopolitics; neoconservatives; platforms; electoral strategies